2018
DOI: 10.1021/acs.oprd.8b00315
|View full text |Cite
|
Sign up to set email alerts
|

Catalyst versus Substrate Control of Forming (E)-2-Alkenes from 1-Alkenes Using Bifunctional Ruthenium Catalysts

Abstract: Here we examine in detail two catalysts for their ability to selectively convert 1-alkenes to (E)-2-alkenes while limiting overisomerization to 3-or 4-alkenes. Catalysts 1 and 3 are composed of the cations CpRu(κ 2 -PN)(CH 3 CN) + and Cp*Ru(κ 2 -PN) + , respectively (where PN is a bifunctional phosphine ligand), and the anion PF 6 − . Kinetic modeling of the reactions of six substrates with 1 and 3 generated firstand second-order rate constants k 1 and k 2 (and k 3 when applicable) that represent the rates of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Selective monoisomerization was also seen with 1,2-epoxy-5-hexene (Table , entry 20) with very little enal formation due to the deactivation of catalyst by decarbonylation of the aldehyde . In entry 18, 5-hexen-2-one suffers from more rapid overisomerization with a maximum yield of monoisomerized product at 66% at 4 h, but monoisomerization is still favored over conjugation by around 3:1 at this point. The conversion of 1,7-octadiene to (2 E ,6 E )-2,6-octadiene requires the migration of two separate double bonds; nevertheless, with higher 2 mol % loading, the doubly monoisomerized product yield reaches >94% within 10 min, but the conjugated diene does not appreciably increase within 24 h.…”
Section: Resultsmentioning
confidence: 99%
“…Selective monoisomerization was also seen with 1,2-epoxy-5-hexene (Table , entry 20) with very little enal formation due to the deactivation of catalyst by decarbonylation of the aldehyde . In entry 18, 5-hexen-2-one suffers from more rapid overisomerization with a maximum yield of monoisomerized product at 66% at 4 h, but monoisomerization is still favored over conjugation by around 3:1 at this point. The conversion of 1,7-octadiene to (2 E ,6 E )-2,6-octadiene requires the migration of two separate double bonds; nevertheless, with higher 2 mol % loading, the doubly monoisomerized product yield reaches >94% within 10 min, but the conjugated diene does not appreciably increase within 24 h.…”
Section: Resultsmentioning
confidence: 99%
“…The butene-containing substrates, in contrast, have only a moderate thermodynamic preference for the E isomer (ca. E : Z 4:1). , …”
Section: Discussionmentioning
confidence: 99%
“…E:Z 4:1). 54,56 The high stereoselectivity of 2-18c6b in the absence of salts is proposed to originate from steric congestion of the crown ether (Scheme 1). Computational studies have shown that the Ir−O bond trans to phenyl is easiest to dissociate, which can open up an alkene binding site.…”
Section: Discussionmentioning
confidence: 99%
“…E:Z 4:1). 5,58 The high stereoselectivity of 2-18c6b in the absence of salts is proposed to originate from steric congestion of the crown ether (Scheme 1). Computational studies have shown that the Ir-O bond trans to phenyl are easiest to dissociate, which can open up a binding site for alkene to bind.…”
Section: Discussionmentioning
confidence: 99%